2017
DOI: 10.22606/mocr.2017.22003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetrazole Regioisomers of Biphenyl as ACE Inhibitors

Abstract: Abstract. Novel angiotensin converting enzyme (ACE) inhibitors were designed based on the structure of commercially available sartans and synthesized by N-alkylation of 5-substituted-1H-tetrazole with 4'-(bromomethyl)-biphenyl-2-carbonitrile gave 1,5-and 2,5-regioisomers of tetrazole. The nitrile group appended to biphenyl nucleus was converted into tetrazole and later the tetrazole was ring transformed into 1,3,4-oxadiazole. The synthesized compounds were screened for the ACE inhibition and some of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These are useful in the treatment of hypertension. Majority of these sartans contain biphenyl‐tetrazole moiety as a common pharmacophore, which is appended to a heterocyclic group via a methylene group [25] . Structure Activity Relationship (SAR) studies of antihypertensive drugs revealed the requirement of following structural features to exhibit the potential activity.…”
Section: Introductionmentioning
confidence: 99%
“…These are useful in the treatment of hypertension. Majority of these sartans contain biphenyl‐tetrazole moiety as a common pharmacophore, which is appended to a heterocyclic group via a methylene group [25] . Structure Activity Relationship (SAR) studies of antihypertensive drugs revealed the requirement of following structural features to exhibit the potential activity.…”
Section: Introductionmentioning
confidence: 99%
“…Fused pyrimidones are reported for their anti‐inflammatory activity . Particularly, pyrido[1,2‐a]pyrimidinone and tetrahedron pyrido[1,2‐a]pyrimidinone are well‐known nucleus in drug discovery since they possess extensive range of biological activity along with anti‐inflammatory property . Moreover, marketed antipsychotic drugs Risperidone and Paliperidone comprise of tetrahedropyrido[1,2‐a]pyrimidin‐4‐one pharmacophore .…”
Section: Introductionmentioning
confidence: 99%